中国风险投资中风险管理研究 = Studies on venture management in venture investment of China - 许宁 Xu, Ning (2008)
Venture investment is the driver for the commercialization of high technology while venture management is the key and the guarantee for the success of venture investment. Taking Chinese venture management in venture investment as object, this paper carefully studied the theories and problems in Chinese venture management and raised corresponding policy proposals, using the methodology that combines normative research and empirical approach together.